The Dilemma of Midwife Criminal Liability: Distinguishing between Malpractice due to Negligence and Medical Risk in Patient Death - Nur Utami Haryati; Happy Yulia Anggraeni (LifeSciFi, 2026)
Midwifery services carry inherent risks, yet adverse outcomes such as maternal and neonatal deaths are often presumed to result from negligence without proper legal assessment, leading to legal uncertainty and potential criminalization of midwives. This study aims to analyze the juridical parameters that differentiate gross negligence from inherent medical risk in midwifery practice. It also examines the boundaries of midwife criminal liability according to Law Number 17 of 2023 concerning Health. The research employed normative legal methods through statute, conceptual, and limited case approaches using secondary data from laws, textbooks, and expert opinions. The findings indicated that midwife liability is based on the principle of fault. Midwives receive full legal protection when they provide services according to their competence, professional standards, standard operating procedures, and with adequate informed consent. Criminal liability only applies when there is proven gross negligence and a clear causal relationship with the patient’s death. A clear distinction between gross negligence and medical risk is essential to protect midwives from unnecessary criminal charges while maintaining patient safety and service quality. This balanced approach is expected to reduce defensive medicine and improve midwifery practice in Indonesia.